The metabolic effects of di (2-ethyl hexyl) phthalate medium dose on lipid profi les in serum and liver tissue (Faculty of Medicine Universitas Indonesia, 2011)
Background: Di (2-ethyl hexyl) phthalate is the most widely used plasticizer in blood storage bag for transfusion. This substance can modify lipid metabolism. This study was aimed to elucidate the metabolic effects of di (2-ethyl hexyl) phthalate medium dose on lipid profiles in serum and liver tissue. Methods: Sprague Dawley rats were fed 1.0 % di (2-ethyl hexyl) phthalate diet (DEHP group, n=5) or a non-supplemented diet (control group, n=5) for 10 days. The rats were allowed to freely access each food. Serum lipid concentrations were measured using enzyme assay kits. Lipids of liver tissues were extracted and the lipid contents were determined. A peach of liver was prepared to determine the activities of malic enzyme and carnitine palmitoyl transferase-1 (CPT-1). Results: Serum lipid concentrations (mg/dL) of DEHP group decreased compared to control (P<0.05). The serum triglyceride (TG) concentrations of control and DEHP groups were respectively (100.5±16.5) and (31.2±1.7); phospholipid (PL), (143.3±7.8) and (88.9±3.2); total cholesterol, (88.7±4.6) and (51.9±2.3). The liver TG content of control and DEHP group (mg/g liver) were respectively, (40.8±4.4) and (23.7±1.3); liver cholesterol were (3.36±0.29) and (2.33±0.23); and the liver PL were (36.5±1.0) and (41.7±0.6). Malic enzyme and CPT-1 activities (nmol/min/mg protein) of DEHP group increased compared to control (P<0.05), in which their increases were approximately by 4.35- and 2.33-folds, respectively. Conclusion: The di (2-ethyl hexyl) phthalate medium dose attenuates lipids secretion from the liver cells into the bloodstream. The increase of liver PL level accompanied with the promotions of malic enzyme and the CPT-1 activities are the key factors of the dietary di (2-ethyl hexyl) phthalate effects in rats to attenuate the lipid secretions from the livers. (Med J Indones 2011; 20:20-6) Keywords: Di (2-ethyl hexyl) phthalate, hyperphospholipids, lipolysis, liver lipids, serum lipids